Ischemic stroke emergent treatment (Irvine, CA : Concept Media, 2000)
Involves a patient with an ischemic brain attack whose early entry into the healthcare system allows him to benefit from the use of new intervention therapies. Cerebral anatomy is explained including descriptions of specific deficits that result from commonly occuring types of eschemic brain attack.
Keywords: Cerebrovascular Accident -- therapy; Cerebrovascular Accident -- diagnosis